Estimation of natural gas optimum allocation to consuming sectors in year 2025 in Iran. Issue 7 (2nd July 2016) - Maroufmashat, Azadeh; Sattari, Sourena
ABSTRACT: Due to a large number of rich natural gas reserves in Iran, and considering the acceptable income from the exports of oil products, the consumption of gas instead of oil products in different consuming sectors seems to be rational. Therefore, in this article, the allocation of natural gas to different sectors such as residential, industries, power plants, transportation, reinjection to oil wells, export, and so forth is estimated based on the three scenarios using a linear programming method for the year 2025 in Iran. The results indicate that if there is no planned consumption management, the allocation of gas in future years will certainly have deficiencies in some sectors in Iran. Consequently, the feasible limit for unit replacement revenue of injection to oil wells is also calculated by sensitivity analysis on the coefficients of linear programming.